Conciencia ciudadana y covid-19 en el municipio de Montería, Córdoba, Colombia (2021)
This work proposes as an academic exercise to make a documentary research that allows society to reflect and know the current problems faced by the health sector of the municipality of Monteria, as a result of the COVID-19 pandemic. The rules given by the national and local state, with the purpose of safeguarding their lives in view of the pandemic, have influenced in the different psychological reactions of the society; this has been reflected in irresponsible behaviors and a true citizen unawareness. It is sought, then, that the population understands that this virus extinguishes human lives regardless of race, color, creed, socio-cultural position; likewise, that they understand that currently the municipality occupies the first place in Colombia where the virus acts with greater lethality. The methodology developed in this work is the bibliographic review, which provided information from official authorities, news media, reliable sources, which allowed truthful information. As for the results of this work, it was observed that the citizens of the municipality are acting without citizen awareness, since they do not comply with the indications and recommendations of social isolation given by the municipal mayor.